Jawabanmu

Jawaban paling cerdas!
2014-04-27T19:22:07+07:00
a. y = cos^2 (3x-2)
    y = {cos(3x - 2)}²
    y ' =  2
cos(3x - 2)(-sin(3x - 2))(3)
         = -3(2sin(3x - 2)cos(3x -2))
         = -3Sin2(3x - 2)
         = -3sin(6x - 4)
 
b. y = sin^2 (2-x) = {sin(2 - x)}²
     y ' = 2{sin(2 - x)(cos(2 - x)(-1)}
          = -2sin(2 - x)cos(2 - x)
         = - Sin2(2 - x)
         = -Sin(4 - 2x)
c. y = x^2 sin 3x
   y '= 2xsin3x + x²(cos3x)3
       = 2sin3x + 3
x²cos3x
d. y = x^2 cos 2x

     y ' = 2xcos2x + x²(-sin2x)2
         = 2xc0s2x  - 2x²sin2x


3 2 3